(untitled) (Studying the History of Higher Education Journal, 2024)
This article traces the stories of four faculty members of the Methodist Theological School in Ohio (MTSO) who, alongside other individuals, were jailed for their integration activism in Jackson, Mississippi in March of 1964. The four faculty members included Van Bogard “Bogie” Dunn, Everett Tilson, Paul Minus, and Jeffrey Hooper. All four were outspoken supporters of racial equality before their arrest, and the persecution they and their fellow protestors faced did not prevent them from voicing their position. Their actions played a pivotal role in organizing for change across the Methodist church and its subsequent desegregation. This historical analysis discusses the events around the arrests in Jackson, Mississippi, and the consequences thereafter. The narrative is based on archival sources and available research on the period.